HUMANIST THEOLOGY: ESTABLISH UMMAH TOWARD A TOLERANCE - Huzain, Muhammad (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The nature of religion has been endlessly discussed by philosophers, theologians, psychologists, and sociologists. They look at different aspects of religion as their interests and their purposes differ. Therefore, they formulate variety of definition of religion. Religion is seen to be difficult to define. But it is necessary to have a clear definition of religion as a starting point for religious studies. But in the globalization era, Muslim need theology basis which is strong. Theology term is to help enrich the muslim knowleadge of Islam. In the thought of Islam theology, means knowleadge which is content in relation beetwen God and the universe. Later, The draft formulation of this, are; How is the book theology in relation of book and religion pluralims? To focus to this formulation, it will be presented many questions, namely: First, How is the theology of consept in the book perspective? The Second, as a book guideline, how is theology implication toward the pluralism religion? Then this writing shows that theology (tauhid) is human awareness on thier believer toward the one god which cover itâs one of essence, action, atribute (characteristic).Â The unity of god essence is a furitification towards God. Yet, The fluralism is to be still unitiedÂ with strong bound, namely bound of essence of God. Â —–Tulisan ini mengkaji konsep ketuhanan dan konsep pluralitas dalam agama Islam. Hal ini penting, karena agama tidak boleh dipahami sebagian-sebagian, tetapi harus secara menyeluruh. Oleh karena itu, masalah agama ini tidak pernah berhenti diperbincangkan oleh para ilmuwan. Dalam rangka memberikan rumusan tentang konsep agama secara benar khususnya kepada para penganutnya dan kepada masyarakat secara umum, maka dalam tulisan ini dikemukakan dua pertanyaan, yaitu: 1.Bagaimana konsep ketuhanan dalam perspektif kitab suci alquran? 2. Sebagai kitab pedoman beragama, bagaimana implikasi ketuhanan terhadap konsep pluralitas? Tulisan ini menunjukkan bahwa tauhid adalah kesadaran manusia akan keberadaan Tuhan yang satu, Tetapi, pluralism akan tetap menjadi kesatuan pijakan yang kuat, yaitu; pijakan kepada Tuhan.